2021
DOI: 10.1016/j.paid.2020.110222
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth (PTG) and posttraumatic depreciation (PTD) across ten countries: Global validation of the PTG-PTD theoretical model

Abstract: This study examined the relationships between posttraumatic growth (PTG) and posttraumatic depreciation (PTD) across 10 countries and assessed the factorial invariance of the standardized inventory assessing PTG and PTD, the PTGDI-X, the expansion of the PTGI-X (Tedeschi et al., 2017). We also investigated the roles of social and cognitive factors in PTG and PTD. Data were collected from participants who identified that their most stressful life experience met the definition of trauma in Australia,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 26 publications
7
79
2
2
Order By: Relevance
“…Recent authors found the independence of these two constructs, which could also have different correlates and lead to opposite wellbeing outcomes [90]. Researchers should treat these as parallel but independent experiences after trauma, which are uniquely related to the well-being of trauma survivors [91].…”
Section: Discussionmentioning
confidence: 99%
“…Recent authors found the independence of these two constructs, which could also have different correlates and lead to opposite wellbeing outcomes [90]. Researchers should treat these as parallel but independent experiences after trauma, which are uniquely related to the well-being of trauma survivors [91].…”
Section: Discussionmentioning
confidence: 99%
“…Aforementioned models of PTG have been studied intensely in recent years (Infurna & Jayawickreme, 2019;Taku et al, 2020). Nevertheless, some alternative theoretical explanations of PTG still have not been addressed adequately in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our assessment did not cover the possibility of simultaneous positive and negative change in the same domain, i.e., survivors might experience an increased sense of reliability of certain others (positive change), but feel disappointed by others (negative change). The newly developed Posttraumatic Growth and Posttraumatic Depreciation Inventory-Expanded version (PTGDI-X, [ 14 ]) offers a validated assessment of positive and negative perceived changes after stressful life events.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may relate to the different psychological underpinnings of perceived positive change, but also to assessment and methodological issues [ 5 ]. Researchers have thus turned away from the exclusive study of positive personality change after stressful life events, and increasingly focus on coexisting positive and negative changes in domains of potential personal growth [ 13 , 14 ]. In this regard, modifications of assessment procedures have been proposed which allow individuals to rate positive or negative changes in each life domain covered by the particular instrument [ 15 ].…”
Section: Introductionmentioning
confidence: 99%